FROST WEATHERING OF SELECTED ROCKS FROM THE TATRA MOUNTAINS - Lubera, Ewa (Quaestiones Geographicae, 2014)
The paper summarises the progress of a frost weathering simulation experiment involving a range of rocks after more than 300 gelation cycles. Samples of granite, conglomerate, sandstone, dolomite, limestone and amphibolite were sourced in the Chochołowska Valley, Tatra Mts. The simulation project, which continues at the Low Temperature Laboratory of the Jagiellonian University, Cracow, is set to quantify the resistance of the rocks to frost weathering by measuring the number of gelation cycles after which the samples are damaged. At the end of the project, the degree of damage will be assessed using the percentage loss of the initial sample weight and a frost weathering indicator. So far, little damage has been recorded overall, with the dolomite samples losing the highest percentage of their initial weight at nearly 6%. The paper also presents results of physical tests of the rocks, including their strength, porosity and density, which provide a useful insight into the interpretation of differences in frost weathering resistance.